1987
DOI: 10.1038/bjc.1987.299
|View full text |Cite
|
Sign up to set email alerts
|

A model to predict the outcome of the bilharzial bladder cancer patient after radical cystectomy

Abstract: Using a discriminant analysis technique to take into account the inter-relationships between the factors, it was found that tumour grade was the most important prognostic factor followed, in order of importance, by tumour stage, renal insufficiency, size of the tumour and lymph node involvement. Moreover, a simplified score for prognosis was determined: X= 10 grade (1 to 3) + 5 stage (1 to 4) + 6 renal insufficiency (Y/N) +1 diameter of the tumour (cm) + 4 lymph node involvement (Y/N). The larger the score, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…It represents 30.3% of all cancer cases treated at the National Cancer Institute in Cairo [18] . Recently, Gouda et al [19] reported a significant decline of the relative frequency of bladder cancer to 11.7%, Bilharzia association from 82.4% to 55.3%, and squamous cell carcinomas from 75.9% to 28.4%.…”
Section: Discussionmentioning
confidence: 99%
“…It represents 30.3% of all cancer cases treated at the National Cancer Institute in Cairo [18] . Recently, Gouda et al [19] reported a significant decline of the relative frequency of bladder cancer to 11.7%, Bilharzia association from 82.4% to 55.3%, and squamous cell carcinomas from 75.9% to 28.4%.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, registration of data in patients' records could not have been influenced by knowledge of the prognostic factors used in the discriminant function. Contrary to the previous study (Rafla et al, 1987), no subject selection was performed. It can thus be assumed that the studied sample was representative of patients with bilharzial bladder cancer diagnosed at the NCI, who underwent radical cystectomy and for whom follow-up was feasible at the NCI of Cairo.…”
mentioning
confidence: 96%
“…
In a previous study (Rafla et al, 1987), it was found that recurrence after radical cystectomy in bilharzial bladder cancer during the first year after the operation is related to tumour grade (G) coded 1, 2 or 3, tumour stage (T) coded 1, 2, 3 or 4, both defined according to the TNM classification of UICC (UICC, 1979), tumour size expressed as the largest diameter in cm (D), presence or absence of renal insufficiency (RI) and of regional lymph node involvement (N), both coded 1.0.A simple linear function X of these factors (X = 10G + 5T + 6RI + ID + 4N) was proposed to discriminate between patients with more than 1 year recurrence-free survival and those who developed a recurrence during the first year after radical cystectomy; recurrence being defined as a local recurrence or appearance of new metastasis as distance. Patients with scores less than or equal to 39 were classified in the good prognosis group, whereas those with scores greater than 39 were classified in the bad prognosis group.

The aim of the present study is to evaluate the qualities of this model on a new sample of bilharzial bladder cancer patients subjected to radical cystectomy, a so called test sample, different from the learning sample which was used to establish the model.

…”
mentioning
confidence: 99%
See 2 more Smart Citations